Patch-Based Techniques in Medical Imaging: First International Workshop, Patch-MI 2015, Held in Conjunction with MICCAI 2015, Munich, Germany, October 9, 2015, Revised Selected Papers - Wu, Guorong; Coupé, Pierrick; Zhan, Yiqiang; Munsell, Brent; Rueckert, Daniel (LNCS sublibrary. SL 6, Image processing, computer vision, pattern recognition, and graphics, 2016)
This book constitutes the thoroughly refereedpost-workshop proceedings of the First International Workshop on Patch-based Techniquesin Medical Images, Patch-MI 2015, which was held in conjunction with MICCAI2015, in Munich, Germany, in October 2015.The 25 full papers presented in this volume werecarefully reviewed and selected from 35 submissions. The topics covered are suchas image segmentation of anatomical structures or lesions; image enhancement;computer-aided prognostic and diagnostic; multi-modality fusion; mono and multimodal image synthesis; image retrieval; dynamic, functional physiologic andanatomic imaging; super-pixel/voxel in medical image analysis; sparsedictionary learning and sparse coding; analysis of 2D, 2D+t, 3D, 3D+t, 4D, and4D+t data.